DAMPAK LITERASI KEUANGAN SYARIAH DAN GAYA HIDUP TERHADAP KONSUMTIVISME GENERASI Z DI ERA DIGITAL - Manshur, Tubagus; Kamil, Islamiah; Prihanto, Hendi (Unversitas Prof. Dr. Moestopo (Beragama), 2025)
The purpose of this study is to examine the impact of Islamic financial literacy and lifestyle on Generation Z consumer levels in the context of the digital era. This generation is susceptible to technology and social media, and often promotes impulsive patterns and excess consumption. These challenges require an educational approach that addresses Islamic financing principles to implement more responsible and sustainable consumption behavior. This study uses a quantitative approach using a questionnaire survey method. In this study, a total of 200 active students between the ages of 17 and 25 were respondents. The data were analyzed using several linear regression techniques to measure the effect of each variable on consumption levels. The results of the analysis show that Islamic financial literacy and lifestyle have a major impact on consumerism, and lifestyle has a more dominant influence. People with high financial literacy in Islamic countries usually have better self-control in dealing with the temptations of digital consumption. The effectiveness of this study highlights the importance of large-scale and systematic Islamic financial education, especially in educational institutions, so that Generation Z becomes smart and wise about the flow of consumption in the digital era.